The relationships between serum fructosamine concentrations and lipid profiles in community-dwelling adults - Peng, You-Fan (Sci Rep, 2017)
We examined the epidemiological associations between serum fructosamine and dyslipidemia indices in community-dwelling adults. Clinical characteristics and lipid profiles were analyzed in 1352 community-dwelling adults. The demographic characteristics and laboratory results were grouped according to the quartiles of serum fructosamine concentrations in all eligible individuals. From the bottom to the top quartile of serum fructosamine, there were graded increases in age, total cholesterol (TC), fasting blood glucose (FBG), total protein (TP), triglyceride (TG), total cholesterol/ high density lipoprotein-cholesterol (TC/HDL-C) and atherogenic index of plasma (AIP). Serum fructosamine was positive correlated with age, TC, FBG, TP, TG, TC/HDL-C and AIP in whole individuals. The positive correlations were then observed in both genders between serum fructosamine and TC, FBG, TP, TG. Two dominant factors were identified by principal component analysis. Logistic regression analysis showed that the two factors were associated with increased serum fructosamine with adjustment for gender, age, body mass index (BMI), FBG and TP. The similar results were observed in males, but not in females. Dyslipidemia tends to contribute to increased serum fructosamine concentrations in study population, suggesting that elevated serum fructosamine may herald an increased risk of cardiovascular disease among community-dwelling adults, especially in males.